Three-dimensional topology-optimized structures for enhanced low-temperature thermal energy storage - Lum, Leymus Yong Xiang (2024)
In this study, a three-dimensional topologically-optimized structure was developed to enhance the thermal energy storage performance of low-temperature phase change materials. The topology of the structure employed in the thermal energy storage device was developed using COMSOL Multiphysics by maximizing heat diffusion in a design domain with a constant temperature plate and adiabatic boundary conditions. The optimized thermal energy storage device was additively manufactured, and its thermal performance was experimentally characterized and compared against two conventional structures as baselines, viz., a plate fin and a pin fin structure. For the first time, this study seeks to determine the sole influence of fin topology on thermal energy storage performance by designing the fins with the same physical parameters, viz., surface area, volume, base plate size, and material. The fin structure volumes were set at approximately 5% of the simulated domain volume and were fabricated by Selective Laser Melting, a metal additive manufacturing technique. The fin structures were experimentally tested under three different constant plate temperatures (65 °C, 70 °C, and 75 °C) using two different phase change materials (RT35 and PEG1000). Their performances were evaluated by comparing the total charging time, melt fraction, and base plate temperature. Our results show that the topology of the optimized fin structure can reduce charging times by up to 9.1% when a constant plate temperature of 65 °C is applied. The topology of the optimized fins also achieved base plate temperatures that were up to 4 °C lower than conventional fins while having a more uniform distribution of heat to the phase change material within the housing. Additionally, by fixing the critical physical parameters of the fin structures, this work also shows that the fin topology plays a significant role in enhancing the melting performance of thermal storage devices.